Identification of Host Range, Biophysical Properties and Electron Microscopic Investigation of the Virus Isolates in Pea: Host Range and Electron Microscopic Investigation of Pea Virus Isolates (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Plant species of families Chenopodiaceae, Leguminosae and Solanaceae (only Petunia 63 hybrida) fall in host range of present virus isolate. Virus isolate found to infect the test plants namely Chenopodium album L., Chenopodium amaranticolor Coaste and Reyn., C. quinoa Wild, C. murale L. Pisum sativum L., Petunia hybrida Vilm, Vicia faba L. However, it could not infect Amaranthus caudatus L., Brassica campestris sp. rapa, Capsicum annuum L., Datura metel L., Datura metel L. var. festuosa, Nicotiana glutinosa L., Nicotiana tabacum L. var. Electron microscopic investigations through ISEM studies revealed that it had flexuous rod shaped particles with close affinity to PSbMV as it resulted in decoration of the virus particles with PSbMV antibodies.